2015
DOI: 10.1038/ncomms9873
|View full text |Cite
|
Sign up to set email alerts
|

MYC-induced reprogramming of glutamine catabolism supports optimal virus replication

Abstract: Viruses rewire host cell glucose and glutamine metabolism to meet the bioenergetic and biosynthetic demands of viral propagation. However, the mechanism by which viruses reprogram glutamine metabolism and the metabolic fate of glutamine during adenovirus infection have remained elusive. Here, we show MYC activation is necessary for adenovirus-induced upregulation of host cell glutamine utilization and increased expression of glutamine transporters and glutamine catabolism enzymes. Adenovirus-induced MYC activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
158
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(170 citation statements)
references
References 30 publications
9
158
1
2
Order By: Relevance
“…Glutamine in MYC-driven cells can be used for de novo proline synthesis 82 or production of the oncometabolite 2-hydroxyglutarate in breast cancer 152 , although the latter finding has not been independently corroborated. Infection by adenovirus or Kaposi’s sarcoma-associated herpesvirus (KSHV) both increase MYC expression and glutamine metabolism 153, 154 , and in the case of KSHV this may be a part of early tumorigenesis that eventually leads to Kaposi’s sarcoma. MYC can also mediate the reprogramming of glutamine metabolism downstream of activation of other oncogenic pathways, including mTOR 155 , and crosstalk with HER2 (also known as ERBB2) and the estrogen receptor (ER) in breast cancer 156 .…”
Section: Oncogenes and Glutamine Metabolismmentioning
confidence: 99%
“…Glutamine in MYC-driven cells can be used for de novo proline synthesis 82 or production of the oncometabolite 2-hydroxyglutarate in breast cancer 152 , although the latter finding has not been independently corroborated. Infection by adenovirus or Kaposi’s sarcoma-associated herpesvirus (KSHV) both increase MYC expression and glutamine metabolism 153, 154 , and in the case of KSHV this may be a part of early tumorigenesis that eventually leads to Kaposi’s sarcoma. MYC can also mediate the reprogramming of glutamine metabolism downstream of activation of other oncogenic pathways, including mTOR 155 , and crosstalk with HER2 (also known as ERBB2) and the estrogen receptor (ER) in breast cancer 156 .…”
Section: Oncogenes and Glutamine Metabolismmentioning
confidence: 99%
“…Noteworthy, Thai et al () demonstrated that human adenovirus infection is associated with the upregulation of glycolytic enzymes through MYC activation, suggesting also an increase of glucose flux toward PPP metabolites. Additionally, a recent report extended this metabolic effect to elevated expression of glutamine transporters and glutamine catabolism enzymes (Thai et al, ). This points out that successful adenovirus infection induces a metabolic environment resembling that of cancer cells, echoing well known similarities between cancer cells and mammalian DNA viruses (Buchkovich et al, ; O'Shea et al, ), as well as the adenovirus oncogenic potential (Endter and Dobner, ; Georgakilas et al, ).…”
Section: Discussionmentioning
confidence: 94%
“…However, targeting GLS more specifically suppresses glutaminolysis, which strengthens the important role of this pathway in HCV replication. Interestingly, glutaminase inhibitors have recently also been shown to display antiviral activity against adenovirus, herpes simplex virus 1, and influenza A, suggesting that glutaminase inhibitors may be interesting to develop as general antivirals because they block the metabolic requirements for progeny virion production.…”
Section: Discussionmentioning
confidence: 99%